Impact of hydraulic and physicochemical factors on spatiotemporal variations of particle-associated bacteria in a drinking water distribution system - Osborne, Erika; Haddix, Madison; Garner, Emily (Frontiers in Water, 2022)
Drinking water distribution systems are critical infrastructure that protect public health by ensuring safe water is transported from centralized treatment facilities to consumers. While growth of bacteria, such as opportunistic pathogens, in distribution system infrastructure is well established as a detriment to water quality, little is known about the role of sediment in conveying bacteria via biofilms throughout these systems. The objective of this study was to quantify the abundance of particle-associated bacteria in a rural drinking water distribution system with a chlorine disinfectant residual. The role of hydraulic and physicochemical factors in influencing the spatiotemporal loading of particle-associated bacteria in the system was also examined. The concentration of particle-associated bacteria averaged 1.28 log10 gene copies per mL, while total bacteria averaged 2.16 log10 gene copies per mL, demonstrating that biofilms formed on the surface of sediment represent a substantial portion of overall loading in the studied distribution system. Total suspended solids concentrations were correlated with particle-associated bacteria, but not total bacteria. Pipe diameter was found to be an important factor associated with the abundance of both total and particle-associated bacteria, as well as total chlorine concentration. Velocity, Reynold's number and the flow regime were also found to be important, as they were associated with both sediment and total bacteria, but not particle-associated bacteria. The results of this study indicate that particle-associated bacteria and total bacteria concentrations often followed disparate trends, demonstrating that their abundance is differentially influenced by a complex combination of physicochemical and hydraulic factors. These findings help to establish sediment as an important conduit for microbial loading in a chlorinated drinking water distribution system.